Implementation of scout inauguration activities in forming student character at Al-Irsyad High School, Banten - Aulia, Nabila Nurul; Rofiroh, Rofiroh; Pajar, Ilham An'nur; Mukhlis, Naufal; Azzahra, Larasatika; Ramdhini, Siti Agni; Setiawati, Eli; Anisa, Nur (Journal of Community Service in Science and Engineering (JoCSE), 2025)
Education plays a critical role in character development. In Indonesia, non-formal education such as scouting supplements formal schooling by fostering holistic student growth. This study explores how scout inauguration activities at Al-Irsyad High School, Banten, contribute to student character formation. Employing a descriptive qualitative approach, the study involved direct observation and interviews with scout instructors and students. The inauguration was structured into five stations: obstacle and rope skills, religious values, etiquette, scouting knowledge, and marching exercises (PBB). Each station focuses on different character values, including discipline, leadership, empathy, independence, and teamwork. The findings show that students gained not only physical and mental resilience but also improved social behavior and moral awareness aligned with the school's vision. The study highlights the importance of sustained scouting programs and recommends integrating character values into daily learning to enhance long-term impact. Pendidikan memegang peranan penting dalam pengembangan karakter. Di Indonesia, pendidikan nonformal seperti kepramukaan melengkapi sekolah formal dengan mendorong pertumbuhan siswa secara holistik. Studi ini mengeksplorasi bagaimana kegiatan pelantikan pramuka di SMA Al-Irsyad, Banten, berkontribusi pada pembentukan karakter siswa. Dengan menggunakan pendekatan kualitatif deskriptif, studi ini melibatkan observasi dan wawancara langsung dengan instruktur dan siswa pramuka. Pelantikan tersebut terstruktur dalam lima pos: keterampilan rintangan dan tali, nilai-nilai agama, etika, pengetahuan kepramukaan, dan latihan baris berbaris (PBB). Setiap pos berfokus pada nilai-nilai karakter yang berbeda, termasuk disiplin, kepemimpinan, empati, kemandirian, dan kerja sama tim. Temuan menunjukkan bahwa siswa tidak hanya memperoleh ketahanan fisik dan mental tetapi juga meningkatkan perilaku sosial dan kesadaran moral yang sejalan dengan visi sekolah. Studi ini menyoroti pentingnya program kepramukaan yang berkelanjutan dan merekomendasikan pengintegrasian nilai-nilai karakter ke dalam pembelajaran sehari-hari untuk meningkatkan dampak jangka panjang.